Rekonstruksi Paradigma Ekonomis dalam Budaya Rambu Solo’ di Toraja Utara - Naomi Sampe (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2020)
Cultural paradigm reconstruction in Economic practical of Rambu Solo’ in North Torajan Regency. The economic cultural transformation in the Torajan funeral ceremony is a kind of reconstruction of how to give or make charity to the grieving family, from pig, buffalo, or any other object and transform into money or capital. These changes are interested to be studied, especially on the impact that inflicted by this cultural reconstruction. This research is using the qualitative approach which runs in descriptive methods. Finally, all data will be exposed to real narratives and qualitative analytic. The results of this research are: 1.the economic cultural reconstruction in the funeral ceremony in North Toraja is leaving some pig or buffalo to resell, the value of the pig or buffalo is exchange into the money. 2.the impact of this economic reconstruction is that the grief burden especially in the economic aspect was lighter and easier. Either the people who come to bring their help (pig, buffalo), shall be more practical and simpler.            AbstrakRekonstruksi Paradigma Budaya Ekonomis dalam Rambu Solo’ di Toraja Utara.  Transformasi budaya ekonomis dalam upacara pemakaman orang Toraja merupakan suatu bentuk pergeseran jenis pemberian/bantuan pada keluarga yang sedang berduka, dari bentuk babi dan kerbau atau materi (benda) menjadi pemberian dalam bentuk uang atau modal. Hal ini menarik untuk diteliti guna mengetahui sejauhmana dampak ekonomis yang ditimbulkan oleh pergeseran budaya ini. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif. Hasil penelitian menunjukkan: Pertama, perubahan ekonomis dalam upacara rambu solo’ di kabupaten Toraja Utara yaitu menyisakan sebagian babi dan kerbau untuk dijual kembali, menggantikan harga babi dan kerbau dengan nominal uang, mengganti pemberian barang dengan uang (amplop). Kedua, dampak perubahan kultur ekonomi dan upacara pemakaman orang Toraja adalah beban ekonomi orang yang melaksanakan upacara rambu solo’ menjadi lebih ringan. Demikian pula dengan keluarga yang datang membawa babi dan barang dapat memakai cara yang lebih praktis, mudah dan murah. Kata kunci: